Efektivitas Media Leaflet Family Planning Terhadap Pengetahuan Akseptor KB Sebagai Upaya Pencegahan Baby Boom - Denny Susilawati; Resi Galaupa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Health services, one of which is Family Planning (KB) services in health facilities, are also affected by Covid-19, it is feared that couples of childbearing age or family planning acceptors might be worried about coming to health facilities, because of that the strategy of using alternative contraception during the Covid-19 pandemic emergency 19 can use short-term contraception with the aim of couples of childbearing age being protected by family planning so as to prevent baby booms. The next strategy is to use appropriate health education. One of them is audio-visual media in the form of video that visually displays images and messages accompanied by sound. But there are also other media that can be used, namely printed media in the form of leaflets.. Research Objectives: To find out the effectiveness of Family Planning Leaflet Media on Knowledge of Family Planning Acceptors as an Effort to Prevent Baby Boom at the Danau Indah Public Health Center in 2023 Research Methods: Quasy Experimental, with a post test design with control group design. The sample is women of childbearing age who have children > 2 people, as many as 30 respondents using a purposive proportional random sampling technique. Level of knowledge using questionnaires about baby boom prevention. post test after using leaflet media. Bivariate analysis using the T-Independent Test. Research Results: Univariate research results The level of knowledge in the control group averaged 8.33 while the knowledge level in the Leaflet group averaged 10.20. The results of the bivariate study obtained a p value (Asymp.Sig.(2-tailed)) which was 0.007, where the value of 0.007 <0.005 (α) showed that Ho was rejected and Ha was accepted Conclusions and Suggestions: Family Planning Leaflet Media is effective on Family Planning Acceptors' Knowledge as an Effort to Prevent Baby Boom at Danau Indah Health Center in 2023. It is hoped that acceptors or prospective acceptors will be more active in seeking information related to contraceptives in an effort to increase their understanding before making decisions, and staff health, especially midwives can apply leaflet-based media in counseling couples of childbearing age who wish to use hormonal and non-hormonal contraception.